1994
DOI: 10.1016/s0022-5347(17)34872-3
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Ontogenic Etiology for Idiopathic Left Varicocele

Abstract: A total of 659 consecutive patients underwent venography for the evaluation of idiopathic left varicocele before sclerotherapy. In 484 cases no valves of the left spermatic vein could be demonstrated, while 172 patients demonstrated competent valves or absent insertions of the left spermatic vein at the typical point on the left renal vein plus retrograde flow over persistent intercardinal anastomoses. Stenosis of the renal vein occurred in 103 patients (15.7%). In only 3 patients was stenosis observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 14 publications
2
76
0
5
Order By: Relevance
“…40,41 Investigations regarding the use of noninvasive sonographic imaging for the confirmation of the nutcracker phenomenon in children and adults have been performed previously. 10,11,[42][43][44] The scope of this study focused on quantitative description and hemodynamic evaluation of the LRV and on the presence of the nutcracker phenomenon (compression of the LRV between the aorta and superior mesenteric artery) 1,[4][5][6][7][9][10] to establish auxiliary diagnostic leads in the determination of the cause of varicocele using noninvasive sonography.…”
mentioning
confidence: 99%
“…40,41 Investigations regarding the use of noninvasive sonographic imaging for the confirmation of the nutcracker phenomenon in children and adults have been performed previously. 10,11,[42][43][44] The scope of this study focused on quantitative description and hemodynamic evaluation of the LRV and on the presence of the nutcracker phenomenon (compression of the LRV between the aorta and superior mesenteric artery) 1,[4][5][6][7][9][10] to establish auxiliary diagnostic leads in the determination of the cause of varicocele using noninvasive sonography.…”
mentioning
confidence: 99%
“…Proposed mechanisms include hypoxia and stasis, elevated testicular temperature, reflux of adrenal catecholamines, and increased oxidative stress. Scrotal temperature is maintained a few degrees below bodycore temperature in order to optimize the environment for normal testicular function by the countercurrent heat exchange first postulated by Dhal and Herrick in 1959 [11]. Impairment of testicular microcirculation has been proposed as a part of the pathologic effects of varicocele.…”
Section: Pathophysiology Of Varicocelementioning
confidence: 99%
“…A second theory is based on the observation that left internal spermatic vein lack functional valves which are more often absent on the left side than the right which can lead regression of blood. Braedel et al [11] demonstrated that the venographic pattern of 659 men with varicoceles showed that 73% of men had absent venous valves. Finally, a third theory suggests that there is partial obstruction of the left spermatic vein between the aorta and superior mesenteric artery ("the nutcracker phenomenon") [10].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomic differences between the left and right internal spermatic vein (accounting for the predominance of left-sided varicocele), the incompetence of venous valves resulting in reflux of venous blood and increased hydrostatic pressure are the most popular theories. 17,18 Increased intraabdominal pressure during childhood and early adolescence may be a predisposing factor in the development of a varicocele. 19 …”
Section: Etiology Of Varicocelementioning
confidence: 99%